Non-thermal processing of pineapple (Ananas comosus [L.] Merr.) juice using continuous pressure change technology (PCT): HS-SPME-GC–MS profiling, descriptive sensory analysis, and consumer acceptance. (30th May 2021) - Vollmer, Kathrin; Czerny, Michael; Vásquez-Caicedo, Ana Lucía; Varona Iglesias, Salima; Frank, Jan; Carle, Reinhold; Steingass, Christof Björn
Graphical abstract: Highlights: First report on the impact of pressure change technology (PCT) on juice volatiles. A total of 128 volatiles was detected by HS-SPME-GC–MS analysis. Significant differences in the total volatiles between the different treatments. Clustering of all four juice types using multivariate statistics (PCA, HCA). Prevention of a fishy off-flavour by thermal pasteurisation and non-thermal PCT. Abstract: The effects of single and twofold continuous pressure change technology (PCT) applications on the volatiles and sensory characteristics of pineapple juice were studied. Fresh and thermally pasteurised juices were additionally characterised. 128 volatiles were tentatively assigned in the four juices. Thermal pasteurisation and a single PCT treatment caused substantial losses in total volatiles of 6 and 20%, respectively. A second PCT passage further reduced the volatiles (36%) and is thus not recommended. PCT-treated samples were clearly distinguished from the remaining juices by principal component analysis. The descriptive sensory profiles, assessed by trained panellists, were not substantially affected by thermal pasteurisation and non-thermal PCT. The fresh juice exhibited a significant fishy off-flavour. In the consumer acceptance test, the thermally pasteurised juice was highly rated compared to both PCT-treated and the fresh juice. This study highlights the potential of PCT to avoid the genesis of off-flavours in fresh-like pineapple juice.